Approximate optimization method as an efficient design methodology for armors under ballistic impacts - Buyuk, Murat; Kurtaran, Hasan; Kan, Cing Dao Steve; Marzougui, Dhafer M. (My University, 2005)
Design optimization of armors under impacts generally follows many computationally costly analyses with predefined design parameters until design objectives and constraints are satisfied. In this paper, an approximate optimization method is proposed as an efficient and effective design optimization methodology for armors. The proposed approximate optimization method, which is implemented in ANSYS Design Optimization Module, is based on coupling of ANSYS parametric preprocessor, 3-D explicit finite element code ANSYS/LS-DYNA and a numerical optimization algorithm over response surface approximations. The power of the approximate optimization method is demonstrated on a laminated armor design problem. A three-layer laminated armor under the high-velocity impact of a projectile is designed to satisfy the minimum penetration of the projectile using the approximate optimization method. The method is systematically able to yield the optimum design with only limited number of finite element analyses. Copyright © 2005 by the American Institute of Aeronautics and Astronautics, Inc. All rights reserved. © 2013 Elsevier B.V., All rights reserved.
46th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics and Materials Conference -- Austin, TX -- 66173
Keywords: Design parameters; Surface approximations; Algorithms; Ballistics; Finite element method; Optimization; Product design; Armor